Error Analysis in Short Fiction Translation from Indonesian into English - Orun, Putri Anugraheli Ramba; Sunra, La; Halim, Abdul (Har Press Indonesia, 2023)
This study aims to determine the types of errors in translating short fiction. The researcher used a qualitative descriptive study with 25 students of English Literature at Makassar State University. Data collection was carried out from a test to find out what types of errors were in the results of each student's translation. Based on the results of the study it was found that there were 4 types of errors in the students' translation results, namely Omission, Addition, Misinformation and Misordering. In Week 1 there were 72 omission errors, 60 addition errors, 82 misinformation and 16 misordering errors. In week 2 there were 53 omission errors, 54 addition errors, 56 misinformation errors and 13 Misordering. The last test in week 3 was Omission with 30 errors, Addition with 39 errors, misinformation with 31 errors and misordering with 3 errors. Finally, the researcher concluded that most students were still confused about using grammar and understanding words because of the influence of the First Language and the lack of competence in the rules or structure of the Second Language.